Perspectives for the Balkans and a Wider European Order - Michael Emerson (The Vienna Institute for International Economic Studies (wiiw), 1999)
CEPS established a template for EU strategy towards the Balkans already during the Kosovo war, and this was refined in the Ljubljana Declaration by the think tanks of the region (with CEPS) in July before the Sarajevo Summit. The subsequent evolution of policy in the region and of the EU and Stability Pact is compared with these proposals. Some parts of the CEPS proposals are developed further. Implications for the rest of the wider Europe are also examined, in search for the defining concepts and mechanisms of an order for the entire European space.
Keywords: 330